(untitled) (Comparative & International Education Series, 2021)
I first pointed to the problems and prospects of Africanizing Historically Black Colleges and Universities (HBCUs) in 2000. Twenty years later, I am revisiting the subject but this time, only to suggest that beyond the symbolism of common heritage, a well-crafted comprehensive African Studies program ubiquitously offered at HBCUs can help mitigate the ‘social distance’ that currently characterizes the relationship between Africans and African Americans. The premise of my argument is that African Studies can be used to reconstitute at HBCUs the spirit of pan-Africanism that engendered such a close relationship between the diaspora and the continent which, by the way, was so helpful in securing independence for many African nations. Regrettably, reminiscent of the past twenty years, in the relentless absence of a robust constituency to advocate for its cause, African Studies continues to take a backseat at HBCUs for lack of serious commitment at the highest level.